Media Framing of Sunni-Shia Tensions in Pakistan - Shah, Syed Zubair (Université d'Ottawa | University of Ottawa, 2019)
Since its founding in 1947, Pakistan has, for the most part, experienced a harmonious relationship between the two major sects of Islam; Sunni and Shia. However, in the wake of the July 1978 seizure of power by General Muhammad Zia-ul-Haq and the 1979 Iranian revolution harmony between the Sunni and Shia began to erode. The sectarian divide between these two groups has social, cultural, and economic implications, the worst of which is marked by increased violence, religious intolerance, and growing numbers of sectarian terror groups. This major research paper (MRP) examines the framing of the divisions between the Sunni and Shia of Pakistan in four of the country’s major domestic newspapers: Dawn, The Nation, Daily Times and Express Tribune. The findings emerging from a combined content and critical discourse analysis of some 145 articles from these newspapers identifies sectarianism, geopolitical and religious extremism as dominant frames. The coverage of the Sunni–Shia tensions reveals a positive coverage for Shia sect and neutral coverage for Sunnis. This finding is important because Sunni Shia violence is a major issue in Pakistan and some studies suggest that media frames this issue by hiding the identity of sectarian victims. Findings emerging from my study contribute to ongoing debate about framing sectarian violence in Pakistan by suggesting that in most cases the identity of the victims is revealed.